The Effects of Adverse Childhood Experiences on Self-Reported Physical and Mental Health Outcomes in Adulthood - Son, Chong-Hwan (Journal of Economics and Behavioral Studies, 2016)
The number of physically and mentally unhealthy days as a measure of health-related quality of life (HRQOL) is used to examine the different effects of the adverse childhood experiences (ACEs) on physical and mental health outcomes. The data, a cross-sectional state-level survey, is obtained from the Behavioral Risk Factor Surveillance System (BRFSS) collected by the Centers for Disease Control and Prevention (CDC) in 2012. Multiple regression analyses are conducted for the study. The results indicate that all individual ACE categories are inversely associated with both physical and mental health, as respondents who exposed to any adverse childhood experience are likely to have physically- and mentally-related poor HRQOL in adulthood. The estimated coefficients for individual ACEs in magnitude on the mental health outcome are, in overall, greater than the estimated coefficients on the physical health outcome. The regression results with accumulative ACE scores indicate that higher levels of the ACE score would affect higher negative health outcomes, such as the dosage effects that appear again in this study. The estimated coefficients of accumulative ACE scores on the mental health outcome exceed the coefficients of ACE scores on physical health outcome for an ACE score of 2 and above. The gap in the estimated coefficients of ACE scores between physically and mentally unhealthy days increases as the ACE score rises. The estimated coefficient at the score ACE8 for the mentally unhealthy days becomes almost twice as large as the coefficient for the physically unhealthy days. Importantly, the negative effects of ACEs on mental health outcomes are significantly greater than the negative effects on physical health outcomes.